2002
DOI: 10.1111/j.1523-1755.2002.kid560.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced adherence of human uremic erythrocytes to vascular endothelium: Role of phosphatidylserine exposure

Abstract: These findings suggest that PS externalization may promote increased uremic erythrocyte adhesion to endothelium, possibly via a direct interaction with matrix thrombospondin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 34 publications
7
32
0
Order By: Relevance
“…We have shown that RBCs from patients on hemodialysis have an increased propensity to adhere to human endothelial cell monolayers, possibly via a direct interaction between PS exposed on the external leaflet of the erythrocyte plasma membrane and thrombospondin in the subendothelial matrix (82). Interestingly, we observed that adhesion of RBCs from uremic patients to the vascular endothelium may modulate NO release by endothelial cultures (83), as previously demonstrated for sickle RBC (84).…”
Section: Rbc-endothelial Cell Interactionsupporting
confidence: 65%
“…We have shown that RBCs from patients on hemodialysis have an increased propensity to adhere to human endothelial cell monolayers, possibly via a direct interaction between PS exposed on the external leaflet of the erythrocyte plasma membrane and thrombospondin in the subendothelial matrix (82). Interestingly, we observed that adhesion of RBCs from uremic patients to the vascular endothelium may modulate NO release by endothelial cultures (83), as previously demonstrated for sickle RBC (84).…”
Section: Rbc-endothelial Cell Interactionsupporting
confidence: 65%
“…The HUVEC utilized in the present study express several adhesion molecules including integrins ␣ v (e.g., ␣ v ␤ 3 , or ␣ v ␤ 5 ) and ␤ 1 , E-and P-selectins, laminin ␣ 5 , vWF, and the adhesion molecules ICAM-1, PECAM-1, or VCAM-1 (3,8) and are thus widely used as model cells for adhesion to the vascular wall (3,8,9,54). Similar to what was shown in earlier studies (57) blocking phosphatidylserines or neutralizing CXCL16 by antibodies decreased but did not fully abrogate adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…HUVEC are a widely used model for cellular interactions with the vascular endothelium under flow conditions with different shear rates representing different size of arteries (3,9,10,57). They were shown to express different adhesion receptors including ␣ v integrins (e.g., ␣ v ␤ 3 or ␣ v ␤ 5 ), ␤ 1 integrins, E-and P-selectins, laminin ␣ 5 , von Willebrand factor, and the adhesion molecules ICAM-1, PECAM-1, or VCAM-1 (3,9).…”
Section: Discussionmentioning
confidence: 99%